The Concept of Application of Renewable Energy in Campus Area - Gaol, Theresia Valentina Lumban; Yanuar, Rustandi; Andriani, Y; Hustina, Inggrit Eva (Universitas Komputer Indonesia, 2023)
Since ancient times, humans have relied heavily on fossil energy. Almost all industrial activities and daily activities are inseparable from dependence on non-renewable energy. Therefore, currently, it is being intensified with the utilization of renewable energy. This research aims to determine the technology-based renewable energy around the campus and open up insights into the use of renewable energy. This research method uses a qualitative descriptive approach. The results of this research are the introduction of renewable energy to the public, especially in the university environment. It is hoped that this research can be applied to renewable energy technology in the university environment. The conclusion from this renewable energy research can find new findings so that they have a contribution to science and education.